Marikana youth: (re)telling stories of ourselves and our place - Moleba, Eliot Mmantidi (My University, 2016)
Prior to and immediately following 1994, South African youth literature has largely focused on atypical groups, especially young people’s participation in political protest and violence (Marks 2001; Ntsebeza 1993; Seekings 1993; Straker 1992; Van Kessel 2000). The challenge for new research is to grapple more broadly with the question of how young people construct ordinary lives and identities amid the changing and transforming socio-cultural, economic and political landscape. As such, this study aimed to focus on the ordinary, quotidian narratives of youth in an extraordinary place of Marikana, where the massacre of striking mineworkers took place in 2012. Face-to-face, individual interviews were conducted with 8 participants (aged between 19 and 31 years) living in Marikana, including people who were born in or had migrated to Marikana. Both structural and thematic analyses were used to analyse the transcribed texts. The structural analysis was used to examine how poverty plays a role in the form of stories told. The thematic analysis focused on the content of the narratives, drawing linkages across participants’ stories to understand how they make meaning of events and experiences in their lives. The themes identified were organised as follows: Marikana (nostalgia about the place of Marikana, and belonging to the place of Marikana), childhood in Marikana and elsewhere (growing up in Marikana, and growing up elsewhere), families and their structure (single-parent headed and transnational families, (grand)mothers as pillars of family, and (inter)generational absence/presence of fathers), education (lack of funds for schooling), and possibilities for the future (dreams and futures deferred, and fantasies of escape). The findings indicate that the trauma and violence of the Marikana Massacre was remarkably marginal in their narratives. Instead, participants stressed poverty as a systemic problem that is far more pervasive in how they (re)produce(d) their stories. This core finding reveals poverty as a perpetual structural violence, a repeated state of trauma that is inflicted on their lives and reflected in their stories. Further findings show that many biological fathers are absent in the lives of their children, mostly due to migration or death. Consequently, sons follow in their fathers’ footsteps, leaving their new families behind (some becoming transnational parents). This produces a prevalent intergenerational absence of fathers in Marikana. As a result, mothers and grandmothers are the main breadwinners and emotional pillars of the family.
This is a research report submitted in partial fulfillment of the requirements for the degree of Masters in Diversity Studies, in the Faculty of Humanities, University of the Witwatersrand, Johannesburg.
Keywords: Poverty--Psychological aspects--South Africa; Discourse analysis, Narrative--Psycological aspects; Young adult literature; Experience--Psychological aspects; Migrant labor; Massacres--South Africa--Rustenburg; Marikana (Rustenburg, South Africa)